Barricades and banners : the Revolution of 1905 and the transformation of Warsaw jewry - Ury, Scott (Stanford studies in Jewish history and culture., 2012)
This book examines the intersection of urban society and modern politics among Jews in turn of the century Warsaw. By focusing on the tumultuous events surrounding the Revolution of 1905 'Barricades and Banners' argues that the metropolitanization of Jewish life led to a need for new forms of community and belonging.